MONTOIA, Xabier. Denboraren izerdia.: Elkar argitaletxea. Donostia. 2003ko martxoa, 221 orrialde - Arozena, Ainhoa (EGAN, 2021)
AINHOA AROZENA. MONTOIA, Xabier. Denboraren izerdia. Elkar argitaletxea. Donostia. 2003ko martxoa, 221 orrialde